Etiolated Stem Branching Is a Result of Systemic Signaling Associated with Sucrose Level. Issue 2 (31st August 2017) - Salam, Bolaji Babajide; Malka, Siva Kumar; Zhu, Xiaobiao; Gong, Huiling; Ziv, Carmit; Teper-Bamnolker, Paula; Ori, Naomi; Jiang, Jiming; Eshel, Dani
Abstract : Hot or cold storage of potato tuber, a swollen stem, induces sucrose accumulation in the parenchyma that enhances branching during sprouting under dark conditions. Abstract: The potato ( Solanum tuberosum ) tuber is a swollen stem. Sprouts growing from the tuber nodes represent loss of apical dominance and branching. Long cold storage induces loss of tuber apical dominance and results in secondary branching. Here, we show that a similar branching pattern can be induced by short heat treatment of the tubers. Detached sprouts were induced to branch by the heat treatment only when attached to a parenchyma cylinder. Grafting experiments showed that the scion branches only when grafted onto heat- or cold-treated tuber parenchyma, suggesting that the branching signal is transmitted systemically from the bud-base parenchyma to the grafted stem. Exogenous supply of sucrose (Suc), glucose, or fructose solution to detached sprouts induced branching in a dose-responsive manner, and an increase in Suc level was observed in tuber parenchyma upon branching induction, suggesting a role for elevated parenchyma sugars in the regulation of branching. However, sugar analysis of the apex and node after grafting showed no distinct differences in sugar levels between branching and nonbranching stems. Vacuolar invertase is a key enzyme in determining the level of Suc and its cleavage products, glucose and fructose, in potato parenchyma. Silencing of the vacuolar invertase-encoding gene led to increased tuber branching in combination with branching-inducing treatments. These results suggest that Suc in the parenchyma induces branching through signaling and not by excess mobilization from the parenchyma to the stem.